1964
DOI: 10.1002/j.1537-2197.1964.tb06637.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Leaf and Bud Formation in Hydrocharis Morsus‐ranae

Abstract: Regular sequences of leaf and bud formation occur in several members of the Hydrocharitaoeae, including Hydrocharis, in which buds are normally formed in the axil of every second leaf of the phyllotactic spiral. Leaf inception begins by periclinal divisions of the inner cells of the 2-layered tunica. Bud formation, which occurs in the apical meristem itself, immediately following the inception of the sub tending leaf primordium, begins by divisions in various planes in the corpus, the 2 tunica layers remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1969
1969
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…(b) Beneficial-Hydrocharis morsus-ranae has proven to be a useful experimental plant for physiological and developmental studies because of its large, clear, unicellular root hairs, ease of cultivation, and regular organogensis (Minshall and Scarth 1952;Minshall 1959;Cutter 1963Cutter , 1964Cutter and Feldman 1970a, b). Its significance in phytosociological work as an indicator species is summarized by Weber-Oldecop (1969) and Podbielkowski and Tomaszewicz (1974).…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…(b) Beneficial-Hydrocharis morsus-ranae has proven to be a useful experimental plant for physiological and developmental studies because of its large, clear, unicellular root hairs, ease of cultivation, and regular organogensis (Minshall and Scarth 1952;Minshall 1959;Cutter 1963Cutter , 1964Cutter and Feldman 1970a, b). Its significance in phytosociological work as an indicator species is summarized by Weber-Oldecop (1969) and Podbielkowski and Tomaszewicz (1974).…”
Section: Namementioning
confidence: 99%
“…The principal means of reproduction is vegetative, through the development of stolon buds and turions (modified overwintering stolon buds) that are formed in the axil of every second leaf (Irmisch 1859; Rohrbach 1871; Loiseau and Nougarède 1963;Cutter 1964).…”
Section: Reproductionmentioning
confidence: 99%
“…Developmental continuity of the meristematic program is indisputable in some cases. For example, in Hydrocharis morsus-ranae the primary shoot apical meristem initiates the primordium, which splits in two parts at the first plastochron forming an axillary meristem and leaf domain (Cutter 1964). In many other species, axillary meristems become anatomically distinguishable in the axils of older leaves that have already separated from the primary shoot apical meristem.…”
Section: Introductionmentioning
confidence: 99%
“…Common primordia have been reported in the initiation of stamen and petal and in multiple stamen initiation (Sattler, 1967), but no other examples of their participation in floral apex initiation are known. Dichotomizing apical meristems are also rare; examples have been reported in Asclepias (Nolan, 1969), Flagellaria (Tomlinson, 1970), and Hydrocharis (Cutter, 1964). (1971) suggested that the saururaceous type of inflorescence was the phylogenetic precursor for the magnoliaceous or winteraceous type solitary flower.…”
Section: Discussion-configuration Changes-rela-mentioning
confidence: 99%